Expression of TXNIP in cancer cells and regulation by 1,25(OH)2D3: is it really the vitamin D3 upregulated protein? - Abu El Maaty, Mohamed A.; Almouhanna, Fadi; Wölfl, Stefan (International journal of molecular sciences, 2018)
Thioredoxin-interacting protein (TXNIP) was originally identified in HL-60 cells as the vitamin D3 upregulated protein 1, and is now known to be involved in diverse cellular processes, such as maintenance of glucose homeostasis, redox balance, and apoptosis. Besides the initial characterization, little is known about if and how 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] induces TXNIP expression. We therefore screened multiple cancerous cell lines of different tissue origins, and observed induction, repression, or no change in TXNIP expression in response to 1,25(OH)2D3. In-depth analyses on HL-60 cells revealed a rapid and transient increase in TXNIP mRNA levels by 1,25(OH)2D3 (3-24 h), followed by a clear reduction at later time points. Furthermore, a strong induction in protein levels was observed only after 96 h of 1,25(OH)2D3 treatment. Induction of TXNIP expression by 1,25(OH)2D3 was found to be dependent on the availability of glucose in the culture medium, as well as the presence of a functional glucose transport system, indicating an inter-dependence of 1,25(OH)2D3 actions and glucose-sensing mechanisms. Moreover, the inhibition of de novo protein synthesis by cycloheximide reduced TXNIP half-life in 24 h, but not in 96 h-1,25(OH)2D3-treated HL-60 cells, demonstrating a possible influence of 1,25(OH)2D3 on TXNIP stability in long-term treatment.